2013
DOI: 10.1038/clpt.2013.81
|View full text |Cite|
|
Sign up to set email alerts
|

In Vitro Methods to Support Transporter Evaluation in Drug Discovery and Development

Abstract: This white paper addresses current approaches and knowledge gaps concerning methods to assess the role of transport proteins in drug/metabolite disposition in humans. The discussion focuses on in vitro tools to address key questions in drug development, including vesicle-and cell-based systems. How these methods can be used to assess the liability of compounds for transporter-based drug-drug interactions (DDIs) in vivo is also explored. Existing challenges and approaches to examine the involvement of transport… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
194
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 236 publications
(196 citation statements)
references
References 71 publications
(89 reference statements)
0
194
0
2
Order By: Relevance
“…The selection of the most appropriate in vitro system will depend on the question/ hypothesis being investigated and constraints such as cost or availability of fresh human kidney tissue. There is some overlap with in vitro models used to investigate drug transport in the liver, as recently reviewed (31). Variability in transporter kinetic parameters observed between different experimental systems and laboratories and its implications will be addressed in more detail in part II.…”
Section: In Vitro Systems To Study Active Transport In Kidneymentioning
confidence: 99%
“…The selection of the most appropriate in vitro system will depend on the question/ hypothesis being investigated and constraints such as cost or availability of fresh human kidney tissue. There is some overlap with in vitro models used to investigate drug transport in the liver, as recently reviewed (31). Variability in transporter kinetic parameters observed between different experimental systems and laboratories and its implications will be addressed in more detail in part II.…”
Section: In Vitro Systems To Study Active Transport In Kidneymentioning
confidence: 99%
“…Nowadays, various in vitro cell culture systems have been used to assess in vitro transporter kinetics for in vivo extrapolation with drug candidates during drug discovery and development (56). For example, plated hepatocytes or cultured hepatocytes between layers of biomatrix are commonly used for in vitro assessment of liver clearance.…”
Section: Examples Of Quantitative Targeted Proteomics For Membrane Trmentioning
confidence: 99%
“…The efflux ratios were all above 2, a value, which has been established as a threshold value for demonstrating the presence of active efflux transporters [24]. The applied substrates and inhibitors were chosen to target P-gp, Bcrp and Mrp's.…”
Section: Efflux Transporter Activity In Bovine Blood-brain Barrier Momentioning
confidence: 99%
“…However, these studies did not demonstrate vectorial transport, as the endothelial cells were cultured on culture plates. Other studies have demonstrated expression and function of P-gp in the bovine brain endothelial cells [19][20][21], but vectorial transport studies have shown efflux ratios below 2 [19][20][21][22][23], which is the generally accepted threshold for concluding active efflux transporter involvement [24]. However, with the exception of the Cecchelli et al [21], these cell culture models displayed transendothelial electrical resistance (TEER) values in the range of 100-300 Ω·cm 2 [20,22,23], which are relatively low compared to the estimated in vivo barrier TEER of 1,000-2,000 Ω·cm 2 [25,26].…”
Section: Introductionmentioning
confidence: 99%